2003
DOI: 10.1037/1076-8998.8.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Job demands, decisional control, and cardiovascular responses.

Abstract: The demand-control model for coronary heart disease was tested using ambulatory blood pressure monitoring. Male patrol officers (N = 118) wore ambulatory blood pressure monitors during 1 of their day shifts with readings taken every 30 min. Following each reading, officers completed a questionnaire using a handheld computer. Significant interactions were obtained between job demands and decisional control for heart rate and pressure rate product such that both variables were highest under conditions of high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
(45 reference statements)
1
23
1
2
Order By: Relevance
“…Men Hypertension 1 (177) / 4 (134,147,157,177) 1 (181 ) / 1 (181 ) 1 (142) / 1 (142) 0 / 0 3 / 6 BP level 5 (129,147,152,172,178) / 11 (129, 138, 145-147, 152, 160, 171, 172, 178, 193) 2 (151, 181) / 6 (125,126,128,151,156,181) 3 (142,161,180) / 3 (142,161,180) 2 (155,182) / 2 (155,182) 12 / 22 +4.52 mm Hg and +1.31-+4.17 mm Hg (153,188,189) and (ii) hypertension OR ranged from 1.62-5.77 (184,185,186,190). In addition, two cross-sectional studies evaluated the separate effect of effort and reward (153,190).…”
Section: Studies On Eri Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Men Hypertension 1 (177) / 4 (134,147,157,177) 1 (181 ) / 1 (181 ) 1 (142) / 1 (142) 0 / 0 3 / 6 BP level 5 (129,147,152,172,178) / 11 (129, 138, 145-147, 152, 160, 171, 172, 178, 193) 2 (151, 181) / 6 (125,126,128,151,156,181) 3 (142,161,180) / 3 (142,161,180) 2 (155,182) / 2 (155,182) 12 / 22 +4.52 mm Hg and +1.31-+4.17 mm Hg (153,188,189) and (ii) hypertension OR ranged from 1.62-5.77 (184,185,186,190). In addition, two cross-sectional studies evaluated the separate effect of effort and reward (153,190).…”
Section: Studies On Eri Modelmentioning
confidence: 99%
“…Confounding might also be present in other studies due to a lack of control for cardiovascular risk factors. For example, some studies did not control for age (125,132,144,146,174) or family history of CVD (61 studies) (23, 44, 124-129, 131-141, 153, 155-159, 161-168, 171, 174, 178, 180, 181, 183, 185-189, 192-194, 214, 223, 224) (tables A-C), which constitute major risk factors for high BP. Residual confounding might also have resulted from the fact that none of the studies on job strain controlled for ERI or vice-versa.…”
Section: (Tables A-c)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand authors have found evidence supporting the models' predictive power with respect to sleep quality (5), cardiovascular responses (25) and stress (4,7). On the other hand, results from Marchand et al (26) demonstrated that the ability to predict variance in mental health outcomes using the model was highly dependent upon the specific outcome measure used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into the health and wellbeing of police has identified several factors that negatively affect the psychosocial health of police and could potentially be incorporated into an occupation specific JDCS model. Those most frequently cited are shift work (27) and harassment and threats of violence (9) Shift work has been associated with a number of adverse health outcomes in a variety of professional groups, including higher levels of work stress (4,8,25), increased risk of cardiovascular disease (17,20,25), fatigue (21,(28)(29)(30)(31) and on-duty injury (3). Shift work in the police force has specifically been associated with a higher incidence of work-related stressors (27), poor sleep quality (5,32,33), increased systolic blood pressure (34) and a higher risk of workplace injury (1,35).…”
Section: Introductionmentioning
confidence: 99%